2011
DOI: 10.1017/s1478951511000010
|View full text |Cite
|
Sign up to set email alerts
|

Parent self-efficacy for managing pain in seriously ill children and adolescents nearing end of life

Abstract: Findings advance knowledge of parent self-efficacy in managing the pain of a child with life-threatening illness. Results can be used to design supportive interventions enhancing parents' caregiving roles during their child's last stages of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The goal of the study was to explore the role of parents' self-efficacy related to pain management for terminally ill children and adolescents. 35 The parents in the study had more negative moods and less vigor than adults in a normative sample as well as higher levels of pain management self-efficacy than previous reports on family caregivers of adult patients. 35 The parents' strain and mood states (mood disturbance, anger, and fatigue) inversely correlated with pain management self-efficacy.…”
Section: Engagement and Communicationmentioning
confidence: 52%
See 2 more Smart Citations
“…The goal of the study was to explore the role of parents' self-efficacy related to pain management for terminally ill children and adolescents. 35 The parents in the study had more negative moods and less vigor than adults in a normative sample as well as higher levels of pain management self-efficacy than previous reports on family caregivers of adult patients. 35 The parents' strain and mood states (mood disturbance, anger, and fatigue) inversely correlated with pain management self-efficacy.…”
Section: Engagement and Communicationmentioning
confidence: 52%
“…35 The parents in the study had more negative moods and less vigor than adults in a normative sample as well as higher levels of pain management self-efficacy than previous reports on family caregivers of adult patients. 35 The parents' strain and mood states (mood disturbance, anger, and fatigue) inversely correlated with pain management self-efficacy. 35 The limitation of this study was that it is a secondary analysis of self-reported data, but the findings will advance future interventions to improve family caregivers' self-efficacy on pain management.…”
Section: Engagement and Communicationmentioning
confidence: 52%
See 1 more Smart Citation
“…Participants rate their degree of certainty on a scale of 10 to 100 (e.g., "How certain are you that you can decrease your pain quite a bit?"). Consistent with literature precedents (e.g., Byrne et al, 2011;Keefe et al, 2003), an average of the three subscales was used to capture all three dimensions of chronic-pain self-efficacy assessed by the CPSS. The CPSS has been found to have strong psychometric properties among older adults living with chronic pain (e.g., Rudy, Weiner, Lieber, Slaboda, & Boston, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…This research finds that parents’ overall or general sense of self-efficacy is positively associated with their children’s general ability to cope with their illness (Byrne et al, 2011; Sofronoff & Farbotko, 2002; Wanamaker & Glenwick, 1998; Wood, Price, Dake, Telljohann, & Khuder, 2010). …”
Section: Introductionmentioning
confidence: 79%